Nursing care of the patient with Patent Ductus Arteriosus in Adult of Transcatheter closure of the patent ductus arteriosus with the PDA occluder device: The Comparative Case Study: การพยาบาลผู้ป่วยโรคหลอดเลือดหัวใจเกินในผู้ป่วยผู้ใหญ่ที่ได้รับการปิดรูรั่ว ด้วยอุปกรณ์พิเศษชนิด PDA occluder device ผ่านสายสวนหัวใจ : กรณีศึกษาเปรียบเทียบ - Supatham , Nongnapat (Journal of Nursing and Health Sciences Nakhon Phanom University, 2024)
Excessive coronary artery disease in adult patients treatment to close the leak with a special device through a cardiac catheter is popular. Because there is a small wound Little blood loss low complications short hospital stay quality nursing care promotes and speeds recovery after treatment. Objective: To study coronary artery disease nursing care in adult patients who have had their leaks closed with a special PDA occluder device through a cardiac catheter according to the nursing process in the previous period during and after the procedure compare 2 case studies. Study design: To compare the treatment of hypertrophic coronary artery disease in adult patients who had the leak closed using a special PDA occluder device through a cardiac catheter who were admitted to Sakon Nakhon Hospital, 2 cases, equipment consisted of the record form collects data from inpatient medical records. comparative analysis of risk factors for coronary heart disease beyond its pathology, signs and symptoms. Nursing treatment and diagnosis nursing process according to the preceding period during and after the procedure. Summary of the study results: Comparison of patients with excess coronary artery disease in adult patients who had the leak closed with a special PDA occluder device through a cardiac catheter. Case 1 had heart disease during pregnancy tired easily tightness in the chest, unable to lie down listening to the heart sound, there was murmur. The echocardiographic examination revealed a coronary artery larger than 9 millimeters, along with a left-to-right short circuit and high blood pressure in the lungs the heart pumps 65 percent of the blood. The second case had congenital heart disease symptoms include easy fatigue, palpitations, murmur on auscultation of the heart. Echocardiographic examination found an excess coronary artery and a short circuit of blood from left to right. The heart's blood pumping rate was 65%. both patients had surgery to close the hole with a special PDA occluder device from comparative analysis. There were 10 identical nursing diagnoses, 1 difference in the second patient: dark urine, hematuria, easy bleeding from receiving antiplatelet and blood clotting drugs. Both patients received DMETHOD treatment and entered a rehabilitation program together with a physical therapist having family and relatives join in caring for patients until they are able to take care of themselves. Conclusion: This study nurses play an important role in evaluating, finding problems, and monitoring for changes in symptoms to cover nursing care before and after cardiac catheterization procedures effectively focus on giving knowledge develop personnel potential continue to improve the quality of care for patients who have their aneurysms closed with special equipment through cardiac catheterization.